Global Characterization of Peripheral B Cells in Parkinson’s Disease by Single-Cell RNA and BCR Sequencing - Wang, Pingping; Luo, Meng; Zhou, Wenyang; Jin, Xiyun; Xu, Zhaochun; Yan, Shi; Li, Yiqun; Xu, Chang; Cheng, Rui; Huang, Yan; Lin, Xiaoyu; Yao, Lifen; et al. (Frontiers in Immunology, 2022)
Immune system plays important roles in the pathogenesis of Parkinson’s disease (PD). However, the role of B cells in this complex disease are still not fully understood. B cells produce antibodies but can also regulate immune responses. In order to decode the relative contribution of peripheral B cell subtypes to the etiology of PD, we performed single cell RNA and BCR sequencing for 10,466 B cells from 8 PD patients and 6 age-matched healthy controls. We observed significant increased memory B cells and significant decreased naïve B cells in PD patients compared to healthy controls. Notably, we also discovered increased IgG and IgA isotypes and more frequent class switch recombination events in PD patients. Moreover, we identified preferential V and J gene segments of B cell receptors in PD patients as the evidence of convergent selection in PD. Finally, we found a marked clonal expanded memory B cell population in PD patients, up-regulating both MHC II genes (HLA-DRB5, HLA-DQA2 and HLA-DPB1) and transcription factor activator protein 1 (AP-1), suggesting that the antigen presentation capacity of B cells was enhanced and B cells were activated in PD patients. Overall, this study conducted a comprehensive analysis of peripheral B cell characteristics of PD patients, which provided novel insights into the humoral immune response in the pathogenesis of PD.